(Invited) Highly Doped Si1-XGex Epitaxy in View of S/D Applications. (8th September 2020) - Rengo, Gianluca; Porret, Clement; Hikavyy, Andriy Yakovitch; Rosseel, Erik; Nakazaki, Nobuya; Pourtois, Geoffrey; Vantomme, Andre; Loo, Roger
Abstract : This contribution focuses on S/D epitaxial layers grown and in-situ doped by chemical vapor deposition, and on the properties of fabricated Ti/p-Si1-x Gex contacts. The Ti/Si1-x Gex :B contact resistivity and the Si1-x Ge1-x :B layer resistivity are both minimized for an optimized range of layer thickness. Both parameters increase as the layer relaxes. Preserving strain in Si1-x Gex :B S/D material is therefore important. The increase in S/D layer resistivity and contact resistivity with increasing layer thickness is, however, not caused by the (small) increase in electrical band gap induced by (partial) layer relaxation. Instead, B incorporation during epitaxial growth is affected by the initiation of layer relaxation and decreases with increasing degree of strain relaxation. This effect is observed for the whole range of Ge concentrations. The reduced B incorporation results in a lower carrier concentration near the layer surface which, in-turn, explains the increase in contact resistivity and layer resistivity.